2014
DOI: 10.1080/10256016.2014.929576
|View full text |Cite
|
Sign up to set email alerts
|

Using stable isotopes to assess dietary changes of American black bears from 1980 to 2001

Abstract: We measured stable carbon and nitrogen isotope ratios in 117 hair samples from American black bears (Ursus americanus) in Great Smoky Mountains National Park, Tennessee, during 1980-2001 from live-trapped bears. We also collected hair from bears with known diets to compare with the wild bears. We hypothesized that biological factors (age, mass, and sex), food availability (hard mast and wild hogs (Sus scrofa)), and nuisance status would influence food selection by black bears and changes in their feeding histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…We found that 7.1% of rehabilitated bears in our study engaged in conflict behavior post‐release, which appears similar to conflict rates in the wild (Pelton and Burghardt , Teunissen van Manen et al ). Similarly, Beecham et al () reported that 6.1% of 424 rehabilitated black bears engaged in conflict behavior, and Binks () reported that 3 of 60 (5%) rehabilitated American black bears were shot by landowners because of conflict behavior.…”
Section: Discussionsupporting
confidence: 85%
“…We found that 7.1% of rehabilitated bears in our study engaged in conflict behavior post‐release, which appears similar to conflict rates in the wild (Pelton and Burghardt , Teunissen van Manen et al ). Similarly, Beecham et al () reported that 6.1% of 424 rehabilitated black bears engaged in conflict behavior, and Binks () reported that 3 of 60 (5%) rehabilitated American black bears were shot by landowners because of conflict behavior.…”
Section: Discussionsupporting
confidence: 85%
“…While there are encompassing theories to begin explaining variation in nitrogen discrimination 31 , we know of no such comprehensive theory for carbon discriminations that likely vary with diet, level of intake, season and animal physiology. Until this issue is resolved, many stable isotope analyses (including this one) have assumed that carbon discrimination is fixed across time and foods 23 36 . Despite the sources of uncertainty inherent to stable isotope analyses, percent salmon in assimilated diets was strongly related to estimates of salmon consumption derived from mercury analysis (saturating model, R 2 = 0.69; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen discriminations used were 5.2 ± 0.5‰ for plant matter and 3.6 ± 0.6‰ for sockeye salmon. We used a constant 3.7 ± 0.2‰ as the carbon discrimination for all foods 23 36 . Our models were structured with bear identification number as a random effect, process error, and uninformative priors.…”
Section: Methodsmentioning
confidence: 99%
“…Teunissen van Manen et al [10] described the use of stable isotopes from fur to compare foraging ecology of wild and captive American black bears (Ursus americanus) that occupy remote areas vs campgrounds and picnic areas in a national park in the southwestern USA. The authors modeled the relationship between δ 13 C and δ 15 N values from bear hair and nine environmental variables.…”
Section: Use Of Stable Isotope Analysis In Wildlife Conservation and mentioning
confidence: 99%